Impact of Student-Centered Collaborative Learning on English Language Achievement in Macedonian High Schools - Isa Spahiu; Agron Zeqiri (European Scientific Journal, ESJ, 2026)
Collaborative learning has increasingly been recognized as a student-centered pedagogical approach that enhances learner interaction, engagement, and communicative competence in English language education. This study investigates the impact of student-centered collaborative learning on English language achievement among Macedonian high school students. The research involved secondary school students and English language teachers and employed questionnaires, classroom observations, and achievement tests as data collection instruments. Quantitative data were analyzed using descriptive statistics and paired-sample t-tests to examine learning gains, while qualitative data provided additional insights into participants’ perceptions. The findings indicate that collaborative learning activities contributed to improvements in students’ vocabulary development, speaking fluency, and overall engagement in English classes. These results suggest that collaborative learning can serve as an effective instructional approach in secondary EFL contexts.